PARENTS' INTERPERSONAL COMMUNICATION PATTERNS TO ADOLESCENT'S CONFIDENCE - Nelyahardi Gutji; Hera Wahyuni; Laila Mufarricha; Dini Humairoh; Ayu Kusniah Sahputri; Fajar Maulana (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
Interpersonal communication carried out by parents is one of the factors that support the growth of self-confidence in children. The purpose of this study was to find out how the pattern of parental interpersonal communication on adolescent self-confidence. This type of research used is descriptive research with a qualitative approach. The data collection method used in this research is the method of observation and interviews. The subjects in this study were 3 students of SMAN 11 Muaro Jambi and their parents. The results of this study indicate that interpersonal communication that is often done by parents and teenagers is very influential on the formation of adolescent self-confidence. Parents who always take the time to communicate with their children, can use the right communication style and can make children more open, which can build self-confidence in their children.